Recognition and decomposition of rib features in thin-shell plastic parts for finite element analysis. Issue 2 (4th March 2018) - Lai, Jiing-Yih; Wang, Ming-Hsuan; Song, Pei-Pu; Hsu, Chia-Hsiang; Tsai, Yao-Chen
ABSTRACT: Feature recognition has been extensively studied for applications in computer-aided design (CAD), computer-aided manufacturing, and computer-aided process planning. However, its application in finite element analysis (FEA) is limited. The primary motivation for applying feature recognition in FEA is to facilitate high-quality mesh generation, which requires not only identifying the geometric entities of a feature but also decomposing and computing the region data. This study proposes an approach based on feature recognition to recognize ribs from a CAD model and decompose them into regions that can be meshed with hexahedral or prismatic meshes. Ribs in a CAD model are generally connected to form a complex structure. A rib recognition algorithm to recognize all faces belonging to a rib structure is proposed, and a rib decomposition algorithm was also developed to decompose the rib structure into rib segment and transition regions. After both types of region were defined, the data to decompose each of them from the CAD model was computed. Several examples are presented to verify the results of the rib recognition and demonstrate the feasibility of the proposed rib decomposition algorithm. GRAPHICAL ABSTRACT: